A Study to Test the Feasibility of Determining Whether Classified Want Ads in Daily Newspapers Are an Accurate Reflection of Local Labor Markets and of Significant Use to Employers and Job Seekers. Final Report - Olympus Research Corp., Salt Lake City, UT.; Olympus Research Corp., Salt Lake City, UT. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The report summarizes findings of a detailed study to test the feasibility of determining whether want ads in daily newspapers are (1) an accurate reflection of local labor markets and (2) of significant use to employers and job seekers. The study found that want ads are a limited source of information about local labor markets. They are of some use to private employment agencies but were of use to only a small percentage of the total number of employers and job seekers in the two cities. Part One introduces the purpose and other factors of the study and presents a synthesis of information emanating from all aspects of the study. Part Two describes six major investigations and the methodology used for analyzing and coding ads. Three major sub-studies were carried out: (1) the content study, an in-depth analysis of the contents of all ads; (2) an overview, an analysis of occupations, industries, advertisers, and location of jobs; and (3) the volume study (charting the number of ads, measurement of space inches, and a count of ads). Chapters also are devoted to: the user survey; the employer survey; and the job-seeker survey. All research instruments are appended. Supportive data are tabulated. (NH)
Sponsoring Agency: Manpower Administration (DOL), Washington, DC. Office of Research and Development.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advertising; Employers; Feasibility Studies; Job Applicants; Labor Market; Newspapers; Publicize; Research Methodology; Surveys; Want Ads; Reports, Research